2013
DOI: 10.1007/s10875-013-9898-x
|View full text |Cite
|
Sign up to set email alerts
|

Decreases in the Numbers of Peripheral Blood Regulatory T Cells, and Increases in the Levels of Memory and Activated B Cells, in Patients with Active Eosinophilic Granulomatosis and Polyangiitis

Abstract: In patients with frequently relapsing EGPA, decreases in Treg cell numbers and increased percentages of activated B cells may induce apoptosis of B cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…75 Conversely, a decreased percentage of CD4 + CD25 high FOXP3 + regulatory T cells has been demonstrated in patients with active EGPA, compared with patients with asthma or chronic eosinophilic pneumonia, 76 and decreases in regulatory T-cell numbers can further differentiate frequently-relapsing from seldom-relapsing EGPA. 77 …”
Section: Immunopathogenesis Of Egpamentioning
confidence: 99%
“…75 Conversely, a decreased percentage of CD4 + CD25 high FOXP3 + regulatory T cells has been demonstrated in patients with active EGPA, compared with patients with asthma or chronic eosinophilic pneumonia, 76 and decreases in regulatory T-cell numbers can further differentiate frequently-relapsing from seldom-relapsing EGPA. 77 …”
Section: Immunopathogenesis Of Egpamentioning
confidence: 99%
“…Ligation of CTLA-4 to CD80 or CD86 or both may trigger the IDO pathway in DCs, in turn activating the transcription factor FOXP3 (which regulates immune functioning) and inhibiting cytokine production by DCs [45]. We demonstrated that patients with EGPA who experience frequent relapses after initial clinical remission have decreased T reg cell counts; increased percentages of B cells positive for CD80, CD27, or CD95; lower CD19 + B cell counts; and lower serum IgG than do those who maintain remission [12]. In contrast, other patients never achieve clinical remission [12].…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that patients with EGPA who experience frequent relapses after initial clinical remission have decreased T reg cell counts; increased percentages of B cells positive for CD80, CD27, or CD95; lower CD19 + B cell counts; and lower serum IgG than do those who maintain remission [12]. In contrast, other patients never achieve clinical remission [12]. These results suggest that an interaction between T reg cells and B cells via the overexpression of costimulatory molecules such as CD80 is related to EGPA disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several lines of evidence also point to a role of B lymphocytes and humoral responses as further contributing to EGPA pathogenesis. Increase in the levels of activated and memory B cells have been found in active EGPA [15]. Myeloperoxidase (MPO)-pANCA are present in 40% of untreated patients [2].…”
Section: Editorialmentioning
confidence: 99%